Alzheimer's Disease-Related Dementias Summit 2016: National research priorities - Corriveau, Roderick A; Koroshetz, Walter J; Gladman, Jordan T; Jeon, Sophia; Babcock, Debra; Bennett, David A; Carmichael, S Thomas; Dickinson, Susan L-J; Dickson, Dennis W; Emr, Marian; Fillit, Howard; Greenberg, Steven M; et al. (Neurology, 2017)
Goal 1 of the National Plan to Address Alzheimer's Disease is to prevent and effectively treat Alzheimer disease and Alzheimer disease-related dementias by 2025. To help inform the research agenda toward achieving this goal, the NIH hosts periodic summits that set and refine relevant research priorities for the subsequent 5 to 10 years. This proceedings article summarizes the 2016 Alzheimer's Disease-Related Dementias Summit, including discussion of scientific progress, challenges, and opportunities in major areas of dementia research, including mixed-etiology dementias, Lewy body dementia, frontotemporal degeneration, vascular contributions to cognitive impairment and dementia, dementia disparities, and dementia nomenclature.